Resistance to Academic Supervision as Disharmony in Intergenerational Teacher Relations - Wardani, Indah Kusuma; Sutopo, Anam; Widyasari, Choiriyah (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: Resistance to academic supervision in Elementary Schools is a reflection of the disharmony of intergenerational relationships between teachers, which is an important issue in improving the effectiveness of supervision and collaboration in educational environments. This study aims to explore the factors that influence resistance to academic supervision and its impact on the quality of teaching and collaboration between teachers in schools. Methodology: Using a qualitative approach, with data collection techniques of interviews conducted with senior and junior teachers from several elementary schools and observations, data triangulation with documentation to collect data related to policies, programs, and results of educational supervision. Results: The results of the study indicate that factors that influence resistance, such as the incompatibility of supervision methods with teaching experience, differences in perception between senior and junior teachers, and the unclear purpose of supervision, need to be considered carefully.Applications/Originality/Value: This study reflects the disharmony of intergenerational relationships between teachers as an important issue in improving the effectiveness of supervision and collaboration in educational environments.